Virtual religion: an approach to a religious and ritual topography of Second Life - Radde-Antweiler, Kerstin (Universitätsbibliothek der Universität Heidelberg, 2008)
Kerstin Radde-Antweiler gives an overview or a cross section about the religious and ritualistic settings within “Second Life” and explores the question why studies in and around Virtual Worlds represent an important issue in the Study of Religions. In her article about “Virtual Religion. An Approach to a Religious and Ritual Topography of Second Life” she introduces the theoretical concept of an “actor-related religious historiography” which tries to take into account the religiousness of the individual actor.